Psychosocial issues of parents of children with cleft lip and palate in relation to their behavioral problems - P Thamilselvan; M Suresh Kumar; Jyotsna Murthy; Manoj Kumar Sharma; N Rajeev Kumar (Wolters Kluwer Medknow Publications, 2015)
Objective: The objective was to identify the behavioral problems if any, in children with cleft lip and palate (CLP) and its relationship with their parents' quality-of-life (QOL) and negative emotions. Design: A cross-sectional explorative study. Setting: Both inpatient and outpatient department of Cleft Care Center, in the hospital. Patients: Participants were 50 parents of CLP children in the age group of 1΍-5 years. Main Outcome Measures: Outcome measures are QOL, Depression, Anxiety, Stress Scale-21, and child behavior checklist. Results: There is a significant positive relationship between internalizing problems such as emotional reactivity, somatic complaints, withdrawn behavior, and on the stress. There was a positive relationship between attention problem of children with parental depression and stress and also between internalizing and externalizing behavioral problems with various aspects of QOL. Conclusion: This study has implications in understanding how CLP children's behavioral problems influence the parent's QOL.